Value of a Nationwide University Network in scaling up telemonitoring: a qualitative study - M Janssen; Marlies P Schijven; S Azam Nurmohamed; E Buskens; NH Chavannes; H.J. Harm Gijsbers; Linda W Dusseljee - Peute; Tom H van de Belt; MN Bekker; MA Buijs; D van Dam; N van Eldik; et al. (BMJ Health & Care Informatics)
Objectives The adoption and subsequent implementation of telemonitoring across university hospital settings is a challenging task. This study provides insight into the perceived value of using a nationwide network to support scaling up telemonitoring in university hospitals.Methods A qualitative approach was used to evaluate the role of the National eHealth network ‘Citrien eHealth programme Implementation and Upscaling (Citrien-2)’. In phase 1, an inventory questionnaire was used to identify successes and lessons learnt. Phase 2 consisted of a semi-structured group interview to develop a deeper understanding about the potential value of the network. Subsequently, we conducted a qualitative content analysis and results were organised into key themes of the non-adoption, abandonment, scale-up, spread and sustainability framework.Results In total, 20 participants responded to our questionnaire, and 7 participants participated in our semistructured group interview. Qualitative analysis revealed 28 themes. The network’s key value is the collaboration and structured approach it promotes. This serves as a foundation for exchanging ideas, identifying both temporary and sustainable funding, and establishing a robust stakeholder position, all of which serve to act as a catalyst for implementation and scaling up of telemonitoring.Discussion Our findings align with known barriers to digital innovation, such as funding and legal issues. Our study shows the value of a nationwide network in overcoming these barriers.Conclusions The Citrien-2 nationwide network contributes to scaling up telemonitoring across university settings. Therefore, we recommend that governments and their funding agencies recognise and embrace the power of these nationwide networks in scaling up digital initiatives.